ANALYZING REGULATORY REFORM IN FOREIGN INVESTMENT THROUGH THE OMNIBUS LAW DRAFT OF LAW - Michael T. Ginting (Problematika Hukum, 2021)
Despite various controversies, the existence of the Omnibus Job Creation Law has resulted in the repeal of at least two regulations and amendments to at least 80 other laws. One of them is Law Number 40 of 2007 concerning Limited Liability Companies (UUPT). The purpose of this research is to examine the concepts and problems contained in the Comprehensive Job Creation Law and their implications for the regulations and the basic concept of a limited liability company. This research is a normative (doctrinal) study of secondary literature research data consisting of primary and secondary legal materials. The findings show that the omnibus law is a legislative method that combines various types of laws into special laws. The Job Creation Bill has several one of the wrong clusters regulating employment. The government is trying to harmonize the three laws so that in line as a result it can put a space for investors to open a business without the need for the risk of overlapping regulations & causing losses to investors.Keywords: Omnibus Law; Legal Implications; Limited company;